Stability of parenteral drugs in hospital circuit - Sarah BOUAMEUR; Aicha BRAHMI; Mimouna BOUNAB; Aicha KHELLIFI (Journal de la Faculté de Médecine d'Oran)
Introduction- Drug stability in healthcare establishments is a recurring problem in practice of hospital pharmacists. Apart from the expired drugs, instabilities are often confirmed by changes in appearance or color observed during drug’s period of validity. The objective of this work was to evaluate the stability and hospital practices likely to induce instabilities of valid parenteral drugs. Materials and methods- Firstly, a cross-sectional descriptive study was carried out over three months in three hospital in western of Algeria. Bad conditions of storage, preparation and administration as well as instabilities have been identified on parenteral drugs with long expiry dates. Secondary, photostability test was carried out under normal conditions of administration after exposure to daylight of both ascorbic acid solution in slow infusion and amoxicillin solution for injection after reconstitution. Results- About 546 parenteral drugs examined, 131 non compliances were identified, including 43% related to poor storage at the pharmacy, 33% related to administration and 24% related to preparation or reconstitution. Among the non-conformities related to storage and those related to administration, exposure to light for photosensitive drugs was predominant at 54% and 53.8% respectively.In addition, photostability study showed reduction of 10% of ascorbic acid content from the 30th minute of infusion and a yellowing of amoxicillin solution after one hour of daylight exposition. Conclusion- These studies showed the importance of having a quality assurance system within the hospital, which will ensure the application of good hospital pharmacy practices and thus guarantee the drug’s stability and efficacy, particularly for liquid parenteral forms.